The findings on initial admission Chest CT scan of patients presenting with an Acute Exacerbation of Chronic Obstructive Pulmonary Disease (AECOPD) - Hamad, Amanj Khdir; Karadakhy, Kamaran Amin; Ahmad, Hakim Mahmoud (Journal of Neonatal Surgery, 2025)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a progressive respiratory disease that is irreversible and characterized by persistent airway obstruction and lung inflammation. Recently due to the advancements in imaging techniques we can have a better analysis of the lung parenchyma, airways, vascular and extrapulmonary manifestations of COPD. Objectives: The primary objective of this study is to assess and classify abnormalities observed on chest CT scans in patients admitted with AECOPD. The aim of the study is to identify parenchymal, airway, and extrapulmonary abnormalities, and to assess their association with the severity of the disease and frequency of exacerbations. Material and Methods: A retrospective analysis was conducted in Sulaimani city on 72 patients (54 male and 18 female), a mean age of 72.5 (56-104 years old), presented with AECOPD (GOLD group E) who underwent CT imaging at hospital admission. The CT scans were reviewed by a radiologist, and findings were categorized. Results: Parenchymal abnormalities were the most common (94.4%), including emphysema (81.7%), bullae (40.8%), ground-glass opacity (33.8%). Airway abnormalities (56.9%) such as bronchial wall thickening (40.8%) and bronchiectasis (21.1%) were frequently observed. Extrapulmonary abnormalities (50%) included coronary artery calcifications (38%) and cardiomegaly (25.4%). There was a significant association between the frequency of exacerbations with severity of emphysema and older age (p-value 0.001 and < 0.001 respectively). Conclusion: Parenchymal abnormalities were the most common findings, including emphysema as the most frequent abnormality. Half of patients had extrapulmonary abnormalities including cardiovascular abnormalities in a significant number of patients. These CT abnormalities had associations with clinical factors such as frequency of exacerbations and age of the patient..